Assessment of the sustainability of the renovation of multi-apartment buildings in residential areas / Daugiabučių namų lietuvoje atnaujinimo darnumo įvertinimas - Saulius Raslanas; Jurgita Alchimovienė (Engineering Structures and Technologies, 2013)
The majority of Lithuanian multi-apartment residential buildings were built before 1993. Moreover, projects of housing renovation and maintenance have not been carried out before 1996. Lack of proper maintenance led to a significant deterioration of multi-apartment buildings. Most of these buildings are neither economic, nor environmentally-friendly and consume a significant amount of heat energy. Six major construction requirements should be satisfied when designing or refurbishing a building.